Inflationary processes under conditions of the Coronavirus pandemic - T. I. Gordievich; P. V. Ruzanov (Омский научный вестник: Серия "Общество. История. Современность")
The inflation dynamics in 2020 was reflected by an indicator of 4,9 %, which was higher than the inflation target of 4 %. The increase in inflation was affected by the complex of internal and external factors. First of all, the Coronavirus situation in Russia affected. Inflationary processes have received new characteristics. The purpose of the article is to analyze the reasons for the price increase in Russia in the context of the Coronavirus pandemic. The article uses comparison methods, factor analysis, and the graphical method. Statistical indicators are used to analyze the factors of inflation. In the course of the analysis, the reasons for the price increase in Russia in 2020–2021 are formulated. Inflationary processes during the pandemic are caused by both traditional and non-traditional factors. The permanent factors include the monetary policy.